LEMBAGA TUNGGAL PENGELOLA REGULASI: DASAR PEMIKIRAN DAN TAWARAN IMPLEMENTASINYA DALAM KETATANEGARAN INDONESIA - Pambudi. S, Rilo; Adhayanto, Oksep; Sucipta, Pery Rehendra (Faculty of Law, Parahyangan Catholic University, 2021)
In this article the author seeks to answer, within the context of the Indonesia state organizational system, why and how Indonesia should establish a single government authority entrusted with supervising the making of ministerial policy regulations or regional government regulations. To that purpose a comparison with other countries is conducted. It is a fact in Indonesia that regulatory powers or function is shared by and among different ministries and by regional governments. The result of which is the problem of sectoral approach and the existence of numerous overlapping and conflicting regulations. To overcome this problem, in consideration of best practices in other countries, the author suggests the establishment of a single government agency entrusted with, inter alia, previewing ministerial or regional government draft regulations.